Intra-population variability in the drought response of a beech (Fagus sylvatica L.) population in the southwest of Europe - Aranda, Ismael; Bahamonde, Héctor Alejandro; Sánchez-Gómez, David (2018)
Phenotypic variability within forest species populations is considered of special relevance for local adaptation under new environments, albeit it has been analyzed to a lesser extent than inter-population phenotypic variability. A common garden study was carried out to assess phenotypic variability in response to water stress in half-sibling families from a marginal population of Fagus sylvatica L. at its south-western range edge distribution in Europe. Two irrigation regimes were applied, well-watered (WW) seedlings and those submitted to weekly cycles of drying–rewatering of growth media. Seedling growth and their leaf functional traits were recorded during the last cycle of water stress. Most of the phenotypic changes were explained by phenotypic plasticity in response to water stress, but there was also a significant effect of family in the expression of some of the studied traits. The relationship of carbon isotope fractioning with gas exchange traits across families under WW conditions did not follow the same pattern as the phenotypic trends. The leaf net photosynthesis across families was modified by the nitrogen content on a leaf mass basis that was in turn correlated positively with leaf nitrogen isotope fractionation. The results point to an important role of leaf nitrogen in determining the intrinsic water-use efficiency (WUE) across families. Variation in WUE was ruled mainly by control of stomatal conductance to water vapor under water stress, but by leaf net photosynthesis under wet conditions. Relatively high inter-family phenotypic variability in growth and functional traits were observed. Within-population phenotypic variability, and the plasticity of some of the studied traits, is of fundamental importance to cope with the harsher environments beech will have to endure in the future at different points in its distribution range.